The Impact of Covid-19 on Rural Areas Students of Pakistan: Moderating Role of HEC Policy and Internet Service - Zahra, Fatima; Gul, Akhtar; Iqbal, Anum; Ghafoor, Tanbila; Ambreen, Ayesha (Asian Journal of Contemporary Education, 2020)
The purpose of this study is to investigate the significant impact of COVID-19 on rural areas students, in case of Pakistan. It is also a check on the moderating role of Higher education commission policy and access of internet services in providing the education facilities to the rural areas. This study adapted in depth analysis techniques and theoretical result find out that corona virus has knocked down the education of rural area student and incompatible role of Higher education of rural areas students. The ultimate evaluation method in education to compete the disaster situation taken by HEC has failed. Here are few suggestions that are quite cheap and easy to acquire in improving the quality of education facilities of distance learning for the rural area students in case of any pandemic or disaster situation. The mean and way of providing the education facility to rural area students should be replaced. In my view, radio is the effective efficient accessible way of communication in providing education. The books or hard copies should be provided to the students. A timetable of delivering lectures should be given to the students along with books. In financial way, HEC should provide books and hard material within the paid fees.